Research on Precise Bibliographic Recommendation of Library Reading Therapy for Low Self-esteem Psychology of Poor College Students Based on AI Profiling (Journal of educational development exploration, 2026)
This article focuses on the issue of inferiority complex among impoverished college students and explores how to utilize AI profiling technology to achieve precise recommendation of reading therapy books. By analyzing the manifestation characteristics and formation mechanism of inferiority complex among impoverished students, combined with the working principle of reading therapy, a personalized recommendation model covering multi-dimensional data collection, dynamic tag system, intelligent matching algorithm and feedback optimization mechanism was constructed. This research aims to provide scientific and precise intervention methods for mental health education of impoverished students, enrich the application practice of "AI+ mental health "in the field of education, and offer new ideas for expanding new directions of university library services and mental health service work in universities.
Keywords: AI portrait; Poor students; Inferiority complex; Reading therapy; Book recommendations; Precise recommendation